KOMPENSASI DAN LINGKUNGAN KERJA: PENGARUHNYA TERHADAP KINERJA KARYAWAN - Gede Ardi Putra Kresmawan; I Gede Putu Kawiana; I Gede Aryana Mahayasa (Warmadewa Management and Business Journal (WMBJ), 2021)
Human resource development is needed to improve employee performance, especially at PT. Inti Dufree Promosindo. The purpose of this study to determine the effect partially and simultaneously compensation and work environment on employee performance at PT. Inti Dufree Promosindo in Denpasar. The population in this study were all employees of PT. Inti Dufree Promosindo in Denpasar as many as 86 people who are divided into 6 shop sections, namely Beauty, Boutique, Fashion Watch, Fine Watch, Food & Liqueur, and Destination. Determination of the sample using saturated sampling technique, where the entire population is sampled. After the instrument test and classical assumption test were carried out, data analysis was carried out using multiple linear regression analysis, determination, t test, and F test. The results of the analysis showed that compensation had a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance. Compensation and work environment simultaneously have a positive and significant effect on employee performance at PT. Inti Dufree Promosindo in Denpasar.